Potential and effective remote work in Brazil: Looking into the gap between metrics - Felipe dos Santos Martins; Geraldo Sandoval Góes; José Antônio Sena Nascimento (EconomiA, 2021)
The main objective of this paper is to seek an explanation for the gap between the estimated remote work potential for Brazil and the remote work observed in the country. For this, at first, the teleworking potential is estimated based on the methodology of Dingel and Neiman (2020) applied to the Brazilian PNAD Contínua research based on the period prior to the beginning of the Covid-19 pandemic. In the research's second stage, this potential is compared with remote work measurement provided by the PNAD Covid-19 survey, which was carried out between May and November 2020. A potential and effective telework gap was found, and we sought to investigate its causes based on the first PNAD Contínua interviews conducted in 2019, which contains information on people's domicile. The results indicate that about a fifth of workers in occupations that can be performed remotely live in households without the necessary means to be in a home office, such as a computer with internet access or even continuous electricity. Thereby, the potential for remote work was refined considering the socioeconomic characteristics of the workers, via the characteristics of the households present in the PNAD Contínua survey, which resulted in a refinement in the initial estimate of the potential for remote work initially carried out here went from 22.7% to 16.7%, significantly closer to that observed in May 2020, whose percentage was 13.3%.
Keywords: J21; J22; J0; 330; Covid-19; Remote work; Work from home in Brazil